CYTOKINE REGULATION OF REGENERATIVE PROCESSES IN PANCREATIC GLAND IN ALLOXAN-INDUCED DIABETIC RATS, AND IT CORRECTION BY 1,3,4-THIADIAZINE COMPOSITION AND LIPOIC ACID - I. G. Danilova; V. V. Emelianov; I. F. Gette; S. Yu. Medvedeva; T. S. Bulavintseva; M. V. Chereshneva; L. P. Sidorova; V. A. Chereshnev; K. V. Sokolova (Медицинская иммунология)
A comprehensive comparative evaluation of the ability of L-17 compound (2-morpholino-5- phenyl-1,3,4-thiadiazine) and antioxidant lipoic acid (LA) to correct blood cytokine levels, metabolic disorders and morphological alterations in pancreas in alloxan-induced diabetes was performed for the first time, using an experimental in vivo model. All the tested compounds have been found to correct hyperglycemia and decreased accumulation of glycated blood proteins. The tested L-17 compound belongs to the 1,3,4-thiadiazine series and is able to correct metabolic disorders occurring in alloxan-induced diabetes comparable to activity of LA antioxidant. However, L-17 reduces the cytokine levels to the values of intact animals, that preventing development of systemic inflammatory response which causes damage of target organs in diabetes mellitus.